FRI0192 Predictors of severe hip involvement in ankylosing spondylitis: data from national inpatient sample. (12th June 2018) - Karmacharya, P.; Poudel, D.R.; Shrestha, P.; Dhital, R.; Davis, J.M.
Abstract : Background: Hip involvement in ankylosing spondylitis (AS) is common (24%–36%), leading to worse functional outcomes. While some cases achieve long-term remission, few develop progressive joint destruction with 5%–8% requiring hip replacement. Although studies in the past have looked at factors associated with severe hip involvement, these remain debated. Objectives: To investigate the factors associated with severe hip disease in patients with AS using a large inpatient US database. Methods: Using the Nationwide Inpatient Sample (NIS) data from 2009–2011, we identified patients with AS based on International Classification of Diseases, Ninth Revision (ICD-9) code 720.0 (first 5 positions) and identified patients with hip surgery with ICD-9 procedural codes 800.5, 801.5, 802.5, 803.5, 804.5, 807.5, 808.5, 809.5, 812.1, 815.1, 815.2, 815.3 (any position). NIS is the largest publicly available all-payer inpatient care database in the United States, sponsored by Agency for Healthcare Research and Quality as a part of Healthcare Cost and Utilisation Project. Univariate and multivariate binomial logistic regressions were used to derive odds ratio for predictors of hip surgery. Statistical analysis was done using STATA version 13.0 (College Station, TX). Results: NIS database from 2009–2011 contained 3538 (weighted counts in the whole US population n=17, 480) patients with AS. Out of those, 190 (weighted n=934) had hip surgery (5.36%). Multivariate binomial regression analysis after controlling for confounders (table 1) showed male sex (OR 2.52, CI 1.65–3.83, p<0.001) and peripheral enthesopathy (OR 8.64, CI 2.48–30.12, p<0.001) to be significantly associated with hip surgery in AS patients, and an inverse relationship with inflammatory bowel disease (IBD) (OR 0.35, CI 0.16–0.76, p=0.01) was seen. Conclusions: Our study found male sex and patients with peripheral enthesopathy to have higher odds of severe hip disease requiring surgery among hospitalised AS patients and significantly lower odds with IBD. Previous studies showed an association with age at onset, delay in diagnosis, bilateral involvement, axial/enthesial disease and severe sacroiliitis. Some of these associations could not be analysed in our study due to lack of individual level patient data. Interestingly, epidemiological factors like smoking and obesity which have been linked to severe disease in PsA, were not found to have any significant association. Routine clinical hip exam and radiological imaging might help to identify high-risk patients. Early therapeutic strategies might be indicated for this specific population to prevent severe hip disease and need for hip replacement surgery. Disclosure of Interest: None declared